(3HMQ GdahGFO aj TQM Yjf GdbhGYOs - (3Ydj Hf YeQ Hf Ydj GdcGJHj GdbRhjfj, fLe GdOjf, hjbGd dg OHjQGf,J (B675 (3g` s ((3eMeO Hf TQgTGg Hf CMeO s)
(3ChdgG (B:s
(3aEf LeGYI ef GdYdeGA GdcHGQ GdPjf TGQcJge ai GdHMK COGe Gddg aVGFdge s
(3BNQgG (B:s
(3hEPG cGf cPdc cGf UObgG eSGhjkG dGLJeGY UObgG hcPHgG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B315 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B159s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs